Antibody response to recombinant human coagulation factor VIII in a new rat model of severe hemophilia A. (8th March 2016) - Lövgren, K. M.; Søndergaard, H.; Skov, S.; Weldingh, K. N.; Tranholm, M.; Wiinberg, B.
Abstract : Essentials Validation of a hemophilia A rat as a translational and predictive model for immunogenicity assessment. Study of the antibody response toward clinically relevant doses of recombinant coagulation factor VIII. A reproducible antibody response was demonstrated when following a human prophylaxis regimen. Antibodies developed after 4–6 intravenous doses and inhibitory titers resembled levels in human patients. Summary: Background: Neutralizing antibodies toward FVIII replacement therapy (inhibitors) are the most serious treatment‐related complication in hemophilia A (HA). A rat model of severe HA (F8 −/− ) has recently been developed, but an immunological characterization is needed to determine the value of using the model for research into inhibitor development. Objectives: Characterize the antibody response towards recombinant human coagulation factor VIII (rhFVIII) in the HA rat, following a human prophylactic dosing regimen. Methods: Two identical studies were performed, which included a total of 17 homozygous HA rats ( F8 −/−, 0% FVIII activity), 12 heterozygous rats ( F8 +/− ), and 12 wild‐type ( F8 +/+ ) rats. All rats received intravenous injections of rhFVIII at 50 IU kg −1 twice weekly for 4 weeks. Predosing blood samples were analyzed for binding and neutralizing anti‐rhFVIII antibodies at weeks 1–7. Results: In both studies, antibodies developed after 4–6 administrations of rhFVIII, and neutralizing antibodies reached levels similar to human patients (range 1–111 BU, median 6.0 BU) at the end of the study. There was no significant difference between the two studies or between genotypes in time to response or levels reached for binding and neutralizing antibodies. Interestingly, early spontaneous bleeds were associated with a faster antibody response. Conclusions: Following intravenous administration of human FVIII, according to a clinical prophylaxis regimen, a robust and reproducible antibody response is seen in this HA rat model, suggesting that the model is useful for intervention studies with the aim of suppressing, delaying, or preventing the inhibitor response. Also, bleeds seem to have an adjuvant effect on the immune response.